Long-term effectiveness and safety of Canakinumab in patients with TRAPS: analysis of the RELIANCE non-interventional study - Blank, Norbert; Schuetz, Catharina; Hufnagel, Markus; Horneff, Gerd; Borte, Michael; Kallinich, Tilmann; Oommen, Prasad T.; Janda, Ales; Henes, Joerg; Weber-Arden, Julia; Stock, Michael; Kuemmerle-Deschner, Jasmin B. (Rheumatology and therapy, 2026)
Introduction: This is an interim analysis of the long-term effectiveness and safety of canakinumab in the tumor necrosis factor receptor-associated periodic syndrome (TRAPS) cohort of the RELIANCE non-interventional study. Methods: From June 2018, the RELIANCE non-interventional study enrolled paediatric (aged ≥ 2 – < 18 years) and adult patients (aged ≥ 18 years) with TRAPS who were receiving canakinumab as part of their routine medical care. Physician- and patient-reported measures of disease activity, dosing patterns and safety were evaluated at baseline and every 6 months until the end-of-study visit.Results: A total of 21 patients with TRAPS were enrolled by the analysis cut-off date of December 2022, of which 61.9% (13/21) were paediatric patients (< 18 years) and 66.7% (14/21) were female. All patients were pre-treated with canakinumab prior to enrolment (median duration of canakinumab treatment prior to study inclusion: 1.2 years). Disease activity, evaluated by physician-reported (physician’s global assessment, disease remission, C-reactive protein, serum amyloid A) and patient-reported (disease activity, fatigue, impact on social life, autoinflammatory disease activity index diary) measures, was generally well controlled throughout the study. At baseline, the majority of patients (71.4%) were receiving the recommended starting dose (SD) of canakinumab, with a more even distribution between the < SD, SD, and > SD dosing schedules observed from month 6. No serious adverse drug reactions were reported. Patients continued to receive vaccinations during long-term treatment with canakinumab. In total, 85.7% (18/21) of patients met the Eurofever/PRINTO classification criteria for TRAPS, 42.9% (9/21) with the presence of a confirmative TNFRSF1A genotype and 42.9% (9/21) without. In total, 14.3% (3/21) of patients did not meet the classification criteria.Conclusions: Data from this interim analysis support the long-term effectiveness and safety of canakinumab for the treatment of TRAPS.
Online veröffentlicht: 26. November 2025
Gesehen am 29.01.2026